Thermodynamic Analysis and Optimization Design of a Molten Salt–Supercritical CO2 Heat Exchanger - Xiaoming Dong; Cancan Zhang; Yuting Wu; Yuanwei Lu; Chongfang Ma (Energies, 2022)
The performance of a heat exchanger is directly related to the energy conversion efficiency of the thermal storage system, and its optimal design is an important method to improve the performance of the heat exchanger. This paper uses the distributed parameter method to analyze the effect of the structural parameters and operating parameters of a heat exchanger on the entransy dissipation rate, the entransy dissipation number, the entransy dissipation heat resistance, entropy production rate, and entropy production number in a molten salt–supercritical CO2 concentric tube heat exchanger. The results show that the entransy dissipation rate and entropy production rate have the same trend, with the structural parameters and operating parameters, as well as the changes in the entransy dissipation number and entransy dissipation thermal resistance, jointly affected by the entransy dissipation rate and the heat exchange. Based on the above indicators, single-objective and multi-objective optimization calculations were carried out. The results show that taking the minimum entropy dissipation number, entransy dissipation heat resistance, and improved entropy production number as the objective functions, and using the heat transfer effectiveness as the evaluation index, the optimization effect is better. The ε value is increased by 41.2%, 39.5%, and 40.3% compared with the reference individual. In the multi-objective optimization, taking the minimum number of entransy dissipation and entropy production as the objective function, and using the efficiency of heat transfer and the pressure drop of the working fluid as the evaluation indicators, the optimization effect is better. Compared with the reference individual, the ε value increased by 23.5%, and <semantics>ΔPh</semantics> and <semantics>ΔPc</semantics> decreased by 51.9% and 32.5%, respectively. This study provides a reference for the optimization of supercritical CO2 heat exchangers by utilizing parameters such as entransy and entropy, which reflect the irreversible loss of the heat transfer process.